2020
DOI: 10.1111/clr.13627
|View full text |Cite
|
Sign up to set email alerts
|

Photofunctionalization as a suitable approach to improve the osseointegration of implants in animal models—A systematic review and meta‐analysis

Abstract: Objectives To determine whether photofunctionalization influences dental implant osseointegration. Material and methods Data on osseointegration rates were extracted from 8 databases, based on bone‐to‐implant contact (BIC) and pushout tests. Internal validity was accessed through the SYRCLE risk of bias tool for animal experimental studies. Meta‐analyses were performed for investigation of the influence of photofunctionalization on implant osseointegration, with a random effect and a confidence interval of 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…There were some disadvantages in pre-clinical studies, which resulted in a risk of bias [ 23 , 24 ]. The quality assessment revealed that no animal study revealed a low risk of bias for all domains [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were some disadvantages in pre-clinical studies, which resulted in a risk of bias [ 23 , 24 ]. The quality assessment revealed that no animal study revealed a low risk of bias for all domains [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were some disadvantages in pre-clinical studies, which resulted in a risk of bias [ 23 , 24 ]. The quality assessment revealed that no animal study revealed a low risk of bias for all domains [ 23 , 24 ]. However, photofunctionalization still showed a benefit in the initial phase of osseointegration in different animal models [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the methods for modifying the surface of titanium implants is a photofunctionalization process in which titanium is irradiated with ultraviolet rays 10) . In animal models, it has been reported that the boneimplant contact rate becomes 90% or more, and the bone-implant bond strength increases 3 times by photofunctionalization treatment 10,11) . It has been reported that photofunctionalization improves the adhesion, proliferation, and functional expression of bone lineage cells early after implantation, even in rat models of osteoporosis 12) .…”
Section: Introductionmentioning
confidence: 99%
“…UV irradiation of the implant surface has been reported to enhance the wettability of the implant surface and promote fast bone healing [ 17 , 18 ]. The effect of photofunctionalization on titanium in improving osseointegration has been documented in animals [ 18 , 19 , 20 ] and human studies [ 21 , 22 ]. Nevertheless, the effect on the peri-implant tissue is not well described in the literature.…”
Section: Introductionmentioning
confidence: 99%